Assessing gel properties of Amur sturgeon (Acipenser schrenckii) surimi prepared by high‐temperature setting (40 °C) for different durations. (6th March 2020) - Gao, Ruichang; Wijaya, Ganesha YA; Yu, Jiamei; Jin, Wengang; Bai, Fan; Wang, Jinlin; Yuan, Li
Abstract: BACKGROUND: Setting effects are different for each fish species tested. There is no published literature on the response of Amur sturgeon ( Acipenser schrenckii ) to increased setting times. This study investigated the effects of high‐temperature setting (40 °C) for different durations on the gel properties of A. schrenckii surimi. As A. schrenckii is a new surimi material, it is also necessary to conduct a sensory evaluation and to report the surimi yields. RESULTS: Increasing setting durations (0.5–1.5 h) significantly improved the gel properties. The best results in terms of molecular forces, gel strength, texture profile analysis (TPA), water holding capacity (WHC), and whiteness were obtained by the gels with setting durations of 1 and 1.5 h. The protein degradation detected as a result of extended setting durations (>2 h) significantly decreased the gel properties. The most inferior gel properties were shown by the gel with setting for 3 h. Protein degradation also resulted in higher cooking loss and poor microstructures. The sensory evaluation indicated that A. schrenckii surimi was generally accepted by the panelists in terms of color, texture, and aroma. The surimi yield obtained in this study was 32.4%, which was similar to commercial surimi and higher than several surimi yields in recent studies. CONCLUSION: Setting durations from 0.5 to 1.5 h can be implemented to improve the properties of A. schrenckii surimi. Extended durations (>2 h) must be avoided. Overall, this work provided some necessary information about setting response, gel properties, sensory evaluation, and surimi yield in A. schrenckii, which will be useful for further studies. © 2020 Society of Chemical Industry